Management of Vannamei Shrimp (Litopenaeus vannamei) Culture in Round Ponds (Millennial Shrimp Farm) at the Brackishwater Aquaculture Development Center (BPBAP) Ujung Batee - Fitriah, Nanda; Kurnia; Humeira; Ali Afwanudin (Journal Informatic, Education and Management (JIEM), 2026)
This study aimed to evaluate the farming management performance of vannamei shrimp (Litopenaeus vannamei) using round ponds (Millennial Shrimp Farm/MSF) at the Brackish Water Aquaculture Center (BPBAP) Ujung Batee. The research was conducted for 90 days by applying POAC (Planning, Organizing, Actuating, and Controlling) management to the production process, including pond preparation, stocking, feeding, water quality control, health monitoring, and harvesting. Data were collected through field observation and descriptive analysis. Based on production evaluations up to DOC 60, the performance parameters obtained included ABW of 8.2–9.0 g/ind, ADG of 0.14–0.33 g/ind/day, biomass of 181–207 kg, SR of 84–89%, and FCR of approximately 1.4. These results indicate efficient production performance, with SR values exceeding farm targets and general success criteria (>70%) and FCR values meeting efficient feed conversion standards (<1.5). MSF technology has the potential to support vannamei farming within limited land areas and can serve as an applicable model for sustainable aquaculture development.